(untitled) (Global Business Management Review (GBMR), 2022)
Earnings management has been the subject of interest in recent years, more profoundly after the 1997/1998 financial crisis and soon after, following the collapse of major corporations such as Enron and WorldCom. Ineffective corporate governance mechanism is believed to be the main cause of earnings management. Based on agency theory, many studies have shown that earnings management is associated with board and audit committee characteristics. Findings (although mixed) provide evidence that boards and audit committees that are independent, knowledgeable, and active are less likely to be involved in earnings management. Another important corporate governance characteristic that has received growing attention is the representation of women on the board of directors (BOD). It is argued that women’s representation on the BOD would alleviate the practice of earnings management. This is because, compared to men, women are believed to have higher ethical values, show less concern for money and advancement in their career, and place greater emphasis on harmonious relationships at the workplace. There is also evidence that top management of American companies with female representation is associated with lower earnings management practice. We believe that it is important that a similar study is conducted in Malaysia. This is because the issue of women holding top posts, both in the public and private sectors in Malaysia has become an important topic in recent years. To date, Malaysia has made significant improvements in promoting women’s interests. Key catalysts towards this development is the establishment of a ministry which specifically promotes the development of women in Malaysia and the adoption of a policy to appoint 30% women at the decision making levels.